Progress of the Discovery Committee's Investigations - G. C. L. B. (Polar Record, 1938)
The publication of a Report on the Progress of the Discovery Committee's Investigations (Discovery Committee, Colonial Office, June 1937) provides a suitable occasion to review briefly the achievements of the last twelve years.